2015
DOI: 10.1037/pspp0000025
|View full text |Cite
|
Sign up to set email alerts
|

Affective contingencies in the affiliative domain: Physiological assessment, associations with the affiliation motive, and prediction of behavior.

Abstract: According to classical motive disposition theory, individuals differ in their propensity to derive pleasure from affiliative experiences. This propensity is considered a core process underlying the affiliation motive and a pervasive cause of motivated behavior. In this study, we tested these assumptions. We presented participants with positive affiliative stimuli and used electromyography (EMG) to record changes in facial muscular activity that are indicative of subtle smiling. We were thus able to physiologic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
83
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 67 publications
(94 reference statements)
7
83
1
Order By: Relevance
“…Supporting its construct validity, studies show strong intercorrelations with other need measurements (e.g. Gerstenberg 2012 or Bilsky andSchwartz 2008) and further show concurrent findings with neurophysiological need measurement (Dufner et al 2015;Quirin et al 2013). Based on these validation results it may be concluded that the PVQ's construct validity is strongly supported.…”
Section: Behavioural Measuresmentioning
confidence: 53%
“…Supporting its construct validity, studies show strong intercorrelations with other need measurements (e.g. Gerstenberg 2012 or Bilsky andSchwartz 2008) and further show concurrent findings with neurophysiological need measurement (Dufner et al 2015;Quirin et al 2013). Based on these validation results it may be concluded that the PVQ's construct validity is strongly supported.…”
Section: Behavioural Measuresmentioning
confidence: 53%
“…These differences in affective reactions to the expression of virtue states could offer an interesting explanation for emergence and development of the observed differences in people's reactivity to perceived changes in the social role context. It could be speculated that affective learning and operational conditioning may play a role in the development of unique situational contingencies (Dufner, Arslan, Hagemeyer, Sch€ onbrodt, & Denissen, 2015;Hill & Roberts, 2010;Shoda et al, 1994). Future longitudinal research would be required to examine this idea by looking into the long-term stability and changes in these situational contingencies.…”
Section: Virtue States and Affective Experiencesmentioning
confidence: 99%
“…Furthermore, it has been used as an index of attitudes toward others (e.g., Brown, Bradley, & Lang, 2006;Dambrun, Desprès, & Guimond, 2003) and oneself (e.g., Buck, Hillman, Evans, & Janelle, 2004) in adults as well as in children (e.g., Armstrong, Hutchinson, Laing, & Jinks, 2007) using supra-as well as subliminal stimuli (e.g., Arndt, Allen, & Greenberg, 2001). For certain questions, facial EMG measures of affect have been found to be more effective and revealing than self-report measures, making this method especially attractive (e.g., Dufner, Arslan, Hagemeyer, Sch€ onbrodt, & Denissen, 2015;Hazlett & Hazlett, 1999;Vanman, Paul, Ito, & Miller, 1997). As such, facial EMG is a widely used tool.…”
mentioning
confidence: 99%
“…This is the goal of the present research. Specifically, we reanalyzed data from two studies, one measuring emotional mimicry (Mauersberger, Blaison, Kafetsios, Kessler, & Hess, 2015) and one measuring affective reactions to pictorial social stimuli (Dufner et al, 2015), to assess both internal consistency and test-retest reliability for these measures. Before describing these studies in detail, some relevant issues regarding the concept of reliability in this context need to be discussed.…”
mentioning
confidence: 99%